2016
DOI: 10.3390/app6030062
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and Functional Properties of Far-Infrared/Anion-Releasing Warp-Knitted Elastic Composite Fabrics Using Bamboo Charcoal, Copper, and Phase Change Materials

Abstract: Elastic warp-knitted composite fabrics with far-infrared emissivity and an anion-releasing property were prepared using bamboo charcoal (BC), copper (Cu), and phase-change material (PCM). The functional composite fabric, which was composed of self-made complex yarns with various twisting degrees and material composition, were created using a rotor twister and ring-spinning technique. The fabric structure was diversified by the feeding modes of weft yarn into a crochet-knitting machine. The twist number of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Far-infrared radiation (FIR), as an environmentally friendly and sustainable energy source, can be utilized in many functional textiles to provide not only thermal comfort but also thermal therapy [1,2,3,4]. According to the annual research and consultation report, a huge commercial market of FIR textile products is emerging, which is expected to explode in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Far-infrared radiation (FIR), as an environmentally friendly and sustainable energy source, can be utilized in many functional textiles to provide not only thermal comfort but also thermal therapy [1,2,3,4]. According to the annual research and consultation report, a huge commercial market of FIR textile products is emerging, which is expected to explode in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Such a result is ascribed to the specific diameter of the GF or the CF (the core layer). The study by Li et al showed that the twist number changed as a result of the variations in the rotary speed, and when the yarns finally reached a firmly compact structure as a result of the continuously increasing rotary speed, their diameter then remains the same without significant differences.…”
Section: Resultsmentioning
confidence: 99%
“…The International Oeko-Tex Association has developed the Sustainable Textile Production (STeP), which authenticates enterprises that meet environmental regulations and corporate social responsibility [1]. On the other hand, people have more demands for textiles, asking for multiple functions, such as electromagnetic shielding [25], far-infrared (FIR) emissivity [6], antibacterial [79], moisture absorbing [10], flame retardant [11], sound absorbent [12], and thermal insulating [1315] properties. Textile products are indispensable and commonly used as garments and furnishings in our daily life, as well as for industrial purposes.…”
Section: Introductionmentioning
confidence: 99%